2012
DOI: 10.1177/2047487312460520
|View full text |Cite
|
Sign up to set email alerts
|

The dysfunction of ammonia in heart failure increases with an increase in the intensity of resistance exercise, even with the use of appropriate drug therapy

Abstract: We conclude that in HF, there is an inefficiency of purine metabolism that increases with increasing exercise intensity, but not with an increase of total volume. These findings suggest that hyperkalemia may play an important role in the disorders of purine metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Dependent on the redox state, E. coli and Lactobacillus plantarum reduce nitrites to ammonia (denitrification) [116] or ammonia is oxidized by Nitrosomonas back to nitrite (nitrification) [117]. Dysregulation of this pathway can lead to pathological accumulation of gut-derived ammonia or nitrite, gut dysbiosis and related cardiovascular problems [118,119,120]. A limitation of this hypothesis is that the presence of ammonia-oxidizing bacteria and archaea is described only in soil, water and plants [121].…”
Section: Gut Bacteria-derived Molecules and The Circulatory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Dependent on the redox state, E. coli and Lactobacillus plantarum reduce nitrites to ammonia (denitrification) [116] or ammonia is oxidized by Nitrosomonas back to nitrite (nitrification) [117]. Dysregulation of this pathway can lead to pathological accumulation of gut-derived ammonia or nitrite, gut dysbiosis and related cardiovascular problems [118,119,120]. A limitation of this hypothesis is that the presence of ammonia-oxidizing bacteria and archaea is described only in soil, water and plants [121].…”
Section: Gut Bacteria-derived Molecules and The Circulatory Systemmentioning
confidence: 99%
“…Moreover, it has been found that NH 3 inhalation in healthy adults results in cerebrovascular vasodilatation without affecting the arterial blood pressure [165]. Finally, patients with HF show increased plasma levels of NH 3 [119,120].…”
Section: Gut Bacteria-derived Molecules and The Circulatory Systemmentioning
confidence: 99%
“…Sarcopenia or loss of skeletal muscle mass is a frequent complication of cirrhosis, advanced heart failure, and chronic lung disease that adversely impacts outcomes . Despite the high clinical significance, there are limited data on the mechanisms of sarcopenia and consequently a lack of effective therapies .…”
mentioning
confidence: 99%
“…S arcopenia or loss of skeletal muscle mass is a frequent complication of cirrhosis, advanced heart failure, and chronic lung disease that adversely impacts outcomes. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) Despite the high clinical significance, there are limited data on the mechanisms of sarcopenia and consequently a lack of effective therapies. (3) Hyperammonemia is a consistent abnormality in cirrhosis due to impaired ureagenesis capacity and portosystemic shunting.…”
mentioning
confidence: 99%
“…Therefore, high ammonia levels signify a state of rapid energy consumption or potential de cits in the aerobic tricarboxylic acid (TCA) cycle. (11)(12)(13)) Accordingly, hyperammonemia can be representative of an insu cient energy supply or defective metabolism in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%